TEACHER AND STUDENTS’ CHALLENGES AND STRATEGIES IN WRITING NARRATIVE TEXT USING GOOGLE CLASSROOM IN A REMOTE AREA - Meita Nurdini Lestari; Dedeh Rohayati (Journal of English Education Program (JEEP), 2022)
This research focused on teacher and students’ challenges and strategies in writing narrative text by using Google Classroom in a remote area. This case study was carried out in an Islamic Senior High School in Malangbong Garut. The writer selected the English teacher and 27 students in class XI IPA-1 as the participants of this study. The first conclusion revealed that the teacher and the students faced challenges in teaching and learning of writing narrative text by using Google Classroom in a remote area, especially in grade eleven of an Islamic Senior High School in Malangbong Garut. The second conclusion revealed that the teacher and students used strategies to solve their challenges in teaching and learning of writing narrative text by using Google classroom in a remote area.